A chrome-plated part fingerprint-resistant coating and preparation method thereof
By constructing a polylacal polycopa adhesion layer on the surface of chrome -plated parts and a protective layer of polyethylene acrylic, and the coordination of silver salt solution, the problem of insufficient chrome surface adhesion is solved, and the performance of fingerprint resistance is achieved. Improvement and extension of service life.
Patent Information
- Application Number
- CN202411648086.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Due to the high energy on the surface of the chrome-plated parts and the tightly arranged structure, the adhesion effect with most organic matter is poor. The adhesion effect of silica is not strong enough, making it difficult to effectively improve the fingerprint resistance of the chrome-plated parts.
Through the principle of molecular bionic science, build a polycopic multicast adhesion layer on the surface of chrome parts, and further polymerize polymel acrylate protective layers on it. Finally Fingerprint performance.
Achieve improvement of fingerprint resistance on the surface of chrome parts, enhance the adhesion strength, improve the tightness and antibacterial performance of the coating, and extend the service life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment of metal material coatings, and in particular relates to a fingerprint-resistant coating for a chrome-plated part and a preparation method thereof. Background Art
[0002] Chrome plating is a process of depositing a layer of chromium metal on a metal surface by electroplating or other chemical methods. Chromium metal can be coated on the surface of a workpiece by electroplating, chemical plating, spraying, etc. to form a decorative and functional coating. The chrome plating layer not only provides surface gloss, but also has excellent functional properties. Common chrome-plated parts include automotive parts, home appliance accessories, bathroom products, decorations, tools, and mechanical parts. Due to its unique coating, chrome-plated parts have a series of excellent physical and chemical properties, mainly including the following aspects: (1) Corrosion resistance: The chromium layer formed on the surface of chrome-plated parts can effectively protect the base metal from oxidation, corrosion and environmental pollution. For example, in a humid environment, the protection of the chromium layer can prevent rusting of metals such as iron and steel; (2) Wear resistance: Chromium metal has a high hardness, which makes chrome-plated parts have good wear resistance and suitable for high wear environments. The chromium layer can effectively reduce the friction on the surface of the parts, thereby increasing their service life; (3) Decorativeness: Chrome-plated parts are often used in fields that require decorative effects, such as automobiles, home appliances, and bathrooms. The chrome-plated surface has a glossy feel and can produce a mirror effect, which is extremely decorative and aesthetically pleasing. (4) Anti-oxidation: Chromium metal can effectively resist oxidation reactions and has high chemical stability. It can still maintain its gloss in high temperature and oxidative environments, and the surface will not easily oxidize and discolor.
[0003] However, during the use of chrome-plated parts, their surfaces are usually finely polished to form a smooth surface, which is easy to absorb tiny oil particles in the air. Human fingertips contain a lot of oil, sweat and salt. When touching the metal surface, these substances will adhere to the metal surface to form fingerprints. Fingerprints are easy to appear, which not only affects the appearance, but also may reduce its corrosion resistance and service life. Therefore, improving the fingerprint resistance of chrome-plated parts has become an important research direction in material surface treatment technology.
[0004] Patent CN112877642A discloses an anti-fingerprint film, a glass product and a preparation method thereof. The anti-fingerprint film and glass product provided by the invention have conductive properties by providing a conductive film layer including In, In oxide, Sn and Sn oxide, thereby eliminating the problem of charge accumulation during use and not affecting the transmittance of the product; the transition layer is provided to better match the hardness of the glass, especially to match the hardness of the tempered glass, and to strengthen the bottom layer of the silicon dioxide layer; the purpose of providing the silicon dioxide layer on the transition layer is to provide more key structures for the deposition and adhesion of the anti-fingerprint film layer, thereby improving the bonding strength and improving the abrasion resistance of the anti-fingerprint film; under the joint action of the conductive film layer, the transition layer, the silicon dioxide layer and the anti-fingerprint film layer, excellent friction resistance, waterproofness, anti-fingerprint performance, bonding strength and a longer service life are obtained.
[0005] Patent CN115161601A discloses a method and equipment for ultrafast laser deposition of diamond-like carbon film, anti-reflection film and anti-fingerprint film. The invention uses femtosecond or picosecond pre-pulses to excite the target material to generate plasma, and based on the interaction of two femtosecond pulses at a small angle in the generated plasma, the target material is re-excited to generate plasma for deposition and coating, thereby achieving rapid coating of diamond-like film, silicon nitride film and other film layers, and anti-fingerprint film coating is carried out in conjunction with the spraying process.
[0006] Patent CN116732507A discloses a galvanized steel passivation liquid and a preparation method thereof. The invention mixes water-based acrylic resin, isopropyl tri(dioctyl pyrophosphate) titanate, ammonium titanate, vanadium oxalate, nano-silica, polyethylene wax, ethanol, regulator A, auxiliary agent B and deionized water, and then dips the mixture on the steel surface to improve fingerprint resistance.
[0007] Since the surface of chrome-plated parts usually presents hydrophobic characteristics, although the surface of silica has silanol groups, it can form a physical adsorption effect with the metal, and then modify the metal surface to prevent fingerprints through the bridging of silica. However, due to the high surface energy of the metal and the tight structural arrangement, the adhesion between the metal and most organic matter is poor, and the adhesion of silica is not strong enough.
[0008] Therefore, it is of great significance to design a method to improve the adhesion between the chrome-plated parts and the surface, thereby achieving fingerprint resistance modification of the chrome-plated parts. Summary of the invention
[0009] In view of the shortcomings of the prior art, the present invention constructs a poly-L-dopa adhesion layer on the surface of the chrome-plated part through the principle of molecular bionics, then further polymerizes the poly-L-dopa to form a polymethacrylate protective layer, and finally further coordinates and crosslinks the silver salt solution to improve the fingerprint resistance of the chrome-plated part. Specifically, the technical solution of the present invention includes the following contents:
[0010] One of the purposes of the present invention is to provide a method for preparing a chrome-plated part anti-fingerprint coating, the preparation method comprising the following steps:
[0011] After the organic siloxane coupling agent is dissolved, deionized water is added and mixed and stirred to form a mixed solution, the pH of the mixed solution is adjusted to 8.5-9.5 with an alkaline solution, and then heated to 40° C.-50° C. for reaction for 2 h-3 h to obtain a silane coupling agent hydrolyzate;
[0012] After the silane coupling agent hydrolyzate is mixed with levodopa, dimethyl sulfoxide is added and stirred to form a mixed system, after the mixed system is evaporated under reduced pressure to remove water, EDC hydrochloride reagent and DMAP reagent are added and the temperature is controlled at 18° C. to 22° C. to react for 15 h to 20 h to obtain modified levodopa;
[0013] The pre-treated chrome-plated part is immersed in the modified levodopa, and the pH of the immersion is adjusted to 8.0-8.5, and the immersion time is 3h-5h;
[0014] After the dipping is completed, the chrome-plated part is immersed in a methacrylate solution with a mass concentration of 30% to 40%, and then an initiator is added and heated to 70°C to 80°C for reaction for 5h to 7h to obtain a polymethacrylate-poly-levodopa-chrome-plated part;
[0015] The polymethacrylate-poly-levodopa-chrome-plated part is immersed in a 0.1 mol / L silver salt solution for 20 h to 24 h to obtain a fingerprint-resistant coating for the chrome-plated part.
[0016] Furthermore, the organosiloxane coupling agent includes vinyl trimethoxysilane or vinyl triethoxysilane. The organosiloxane coupling agent needs to contain a carbon-carbon double bond. The role of the carbon-carbon double bond is to load the acrylate solution on poly-L-dopa through a double bond polymerization reaction to form a dense protective layer.
[0017] Furthermore, the mass ratio of the organic siloxane coupling agent to deionized water is 1:4-6, and the amount of deionized water is as large as possible to ensure that the hydrolysis is complete and re-condensation is difficult.
[0018] Furthermore, the pH value of the silane coupling agent hydrolyzate is 5.5-6.0.
[0019] Furthermore, the mass ratio of the silane coupling agent hydrolyzate: levodopa: EDC hydrochloride reagent: DMAP reagent is 2-3: 0.1: 0.05-0.1: 0.05-0.1.
[0020] Furthermore, the pre-treated chrome-plated part is obtained by grinding the surface of the chrome-plated part with sandpaper and then washing and drying it with acetone and water.
[0021] Furthermore, the methacrylate solution includes methyl methacrylate solution or ethyl methacrylate solution.
[0022] Furthermore, the initiator includes azobisisobutyronitrile or benzoyl peroxide.
[0023] Furthermore, the mass ratio of the methacrylate solution to the initiator is 1:0.005-0.01.
[0024] Furthermore, the silver salt solution includes silver nitrate solution.
[0025] A second object of the present invention is to provide a chrome-plated part fingerprint-resistant coating prepared by the method for preparing a chrome-plated part fingerprint-resistant coating.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The invention obtains the function of firmly adhering to the surface of objects such as reefs and hulls by relying on the catechol and amino structures with strong cross-linking self-polymerization of marine organism mussels. According to the mechanism of molecular bionics, levodopa is used as a raw material, the carboxyl structure on the levodopa is activated, and then condensed with the organic siloxane coupling agent with carbon-carbon double bonds after hydrolysis, so that the organic siloxane coupling agent is introduced into the levodopa to obtain modified levodopa. The chrome-plated part is immersed in the modified levodopa solution, and the modified levodopa can self-polymerize in an alkaline environment to form poly-levodopa with a strong cross-linking network structure. The poly-levodopa forms a physical-chemical interaction layer with good adhesion by generating a strong adsorption effect with the surface of the chrome-plated part through the hydroxyl and amino groups on its own structure, thereby improving the adhesion strength. Subsequently, the chrome-plated part with the poly-levodopa structure adhered thereto is immersed in a methacrylate solution again, and the carbon-carbon double bonds on the poly-levodopa and the carbon-carbon double bonds of the methacrylate are chemically copolymerized by an initiator, so that the poly-levodopa surface is further loaded with the polymethacrylate structure to form a polyacrylate-poly-levodopa-chrome-plated part structure, and the polymethacrylate can form a dense structure through hydrogen bonding, thereby improving the anti-fingerprint performance, and finally immersed in a silver salt solution for further coordination and cross-linking to obtain a chrome-plated part anti-fingerprint coating. Through the strong adhesion of poly-levodopa, and the coordinated cooperation of hydrogen bond cross-linking adsorption, chemical copolymerization and metal coordination, not only the density of the surface coating of the chrome-plated part is synergistically improved, thereby achieving anti-fingerprint protection for the chrome-plated part, but also the silver ions in the silver salt solution can be fixed in the anti-fingerprint coating of the chrome-plated part through metal coordination, so that it has antibacterial properties. The increase in antibacterial properties can reduce the erosion of bacteria on the anti-fingerprint coating, which plays an important role in extending the service life of the anti-fingerprint coating. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0029] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods. Embodiment 1:
[0030] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0031] 200g of vinyltrimethoxysilane was dissolved in an acetone solution of equal mass, and then 800g of deionized water was added and stirred to form a mixed solution. Sodium hydroxide solution was added dropwise to the mixed solution to adjust the pH to 8.5, and then the mixed solution was heated to 40°C for hydrolysis reaction for 2h. After the hydrolysis was completed, the pH value of the solution was adjusted to 5.5 to obtain a vinyltrimethoxysilane hydrolyzate.
[0032] Weigh 400g of vinyl trimethoxysilane hydrolyzate, add 20g of levodopa to it and mix and stir until levodopa is dissolved, then add 400g of dimethyl sulfoxide and mix and stir to form a mixed system, then evaporate under reduced pressure to remove water in the mixed system, then add 10g of EDC hydrochloride reagent and 10g of DMAP reagent and mix and stir evenly, control the temperature of the whole system at 20±2°C, and time the reaction for 15h. After the reaction is completed, dialyze with a dialysis bag with a molecular weight cutoff of 500Da and collect the internal liquid in the dialysis bag, then purify with column chromatography, and then dry to remove water to obtain modified levodopa.
[0033] After the chrome-plated parts were polished with sandpaper, they were rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in modified L-DOPA, and the pH of the immersion was adjusted to 8.0, and then the immersion was timed for 3 hours. After the immersion was completed, the treated chrome-plated parts were taken out and completely immersed in a methyl methacrylate solution with a mass concentration of 30%, and then azobisisobutyronitrile was added according to 0.005 times the mass of the methyl methacrylate solution, mixed and stirred, and heated to 70°C for catalytic reaction for 5 hours. After the reaction was completed, the polymethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polymethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in a 0.1mol / L / silver nitrate solution for 20 hours to obtain a fingerprint-resistant coating for the chrome-plated parts. Embodiment 2:
[0034] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0035] 200g of vinyltrimethoxysilane was dissolved in an acetone solution of equal mass, and then 900g of deionized water was added and stirred to form a mixed solution. Sodium hydroxide solution was added dropwise to the mixed solution to adjust the pH to 8.5, and then the mixed solution was heated to 40°C for hydrolysis reaction for 2h. After the hydrolysis was completed, the pH value of the solution was adjusted to 5.5 to obtain a vinyltrimethoxysilane hydrolyzate.
[0036] Weigh 450g of vinyl trimethoxysilane hydrolyzate, add 20g of levodopa to it and mix and stir until levodopa is dissolved, then add 400g of dimethyl sulfoxide and mix and stir to form a mixed system, then evaporate under reduced pressure to remove water in the mixed system, then add 12g of EDC hydrochloride reagent and 12g of DMAP reagent and mix and stir evenly, control the temperature of the whole system at 20±2°C, and time the reaction for 16h. After the reaction is completed, dialyze with a dialysis bag with a molecular weight cutoff of 500Da and collect the internal liquid in the dialysis bag, then purify with column chromatography, and then dry to remove water to obtain modified levodopa.
[0037] After the chrome-plated parts were polished with sandpaper, they were rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in modified L-DOPA, and the pH of the immersion was adjusted to 8.0, and then the immersion was timed for 3 hours. After the immersion, the treated chrome-plated parts were taken out and completely immersed in a methyl methacrylate solution with a mass concentration of 32%, and then azobisisobutyronitrile was added according to 0.006 times the mass of the methyl methacrylate solution, mixed and stirred, and heated to 72°C for catalytic reaction for 5 hours. After the reaction, the polymethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polymethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in a 0.1mol / L / silver nitrate solution for 20 hours to obtain a fingerprint-resistant coating for the chrome-plated parts. Embodiment 3:
[0038] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0039] 200g of vinyltrimethoxysilane was dissolved in an acetone solution of equal mass, and then 1000g of deionized water was added and stirred to form a mixed solution. Sodium hydroxide solution was added dropwise to the mixed solution to adjust the pH to 9.0, and then the mixed solution was heated to 45°C for hydrolysis reaction for 2.5h. After the hydrolysis was completed, the pH value of the solution was adjusted to 5.5 to obtain a vinyltrimethoxysilane hydrolyzate.
[0040] Weigh 500g of vinyl trimethoxysilane hydrolyzate, add 20g of levodopa to it and mix and stir until levodopa is dissolved, then add 400g of dimethyl sulfoxide and mix and stir to form a mixed system, then evaporate under reduced pressure to remove water in the mixed system, then add 14g of EDC hydrochloride reagent and 14g of DMAP reagent and mix and stir evenly, control the temperature of the whole system at 20±2°C, and time the reaction for 17h. After the reaction is completed, dialyze with a dialysis bag with a molecular weight cutoff of 500Da and collect the internal liquid in the dialysis bag, then purify with column chromatography, and then dry to remove water to obtain modified levodopa.
[0041] After the chrome-plated parts were polished with sandpaper, they were rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in modified L-DOPA, and the pH of the immersion was adjusted to 8.0, and then the immersion was timed for 4 hours. After the immersion, the treated chrome-plated parts were taken out and completely immersed in a methyl methacrylate solution with a mass concentration of 34%, and then azobisisobutyronitrile was added according to 0.007 times the mass of the methyl methacrylate solution, mixed and stirred, and heated to 74°C, and the catalytic reaction was carried out for 6 hours. After the reaction, the polymethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polymethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in a 0.1mol / L / silver nitrate solution for 21 hours to obtain a fingerprint-resistant coating for the chrome-plated parts. Embodiment 4:
[0042] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0043] 200g of vinyl triethoxysilane was dissolved in an acetone solution of equal mass, and then 1100g of deionized water was added and stirred to form a mixed solution. Sodium hydroxide solution was added dropwise to the mixed solution to adjust the pH to 9.0, and then the mixed solution was heated to 45°C for hydrolysis reaction for 2.5h. After the hydrolysis was completed, the pH value of the solution was adjusted to 6.0 to obtain a vinyl triethoxysilane hydrolyzate.
[0044] Weigh 550g of vinyl triethoxysilane hydrolyzate, add 20g of levodopa to it and mix and stir until levodopa is dissolved, then add 400g of dimethyl sulfoxide and mix and stir to form a mixed system, then evaporate under reduced pressure to remove water in the mixed system, then add 16g of EDC hydrochloride reagent and 16g of DMAP reagent and mix and stir evenly, control the temperature of the whole system at 20±2°C, and time the reaction for 18h. After the reaction is completed, dialyze with a dialysis bag with a molecular weight cutoff of 500Da and collect the internal liquid in the dialysis bag, then purify with column chromatography, and then dry to remove water to obtain modified levodopa.
[0045] After the chrome-plated parts were polished with sandpaper, they were rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in modified L-DOPA, and the pH of the immersion was adjusted to 8.5, and then the immersion was timed for 4 hours. After the immersion, the treated chrome-plated parts were taken out and completely immersed in a 36% mass concentration of ethyl methacrylate solution, and then benzoyl peroxide was added according to 0.008 times the mass of the ethyl methacrylate solution, mixed and stirred, and heated to 76°C, and the catalytic reaction was 6 hours. After the reaction, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in a 0.1mol / L / silver nitrate solution for 22 hours to obtain a fingerprint-resistant coating for the chrome-plated parts. Embodiment 5:
[0046] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0047] 200g of vinyl triethoxysilane was dissolved in an acetone solution of equal mass, and then 1200g of deionized water was added and stirred to form a mixed solution. Sodium hydroxide solution was added dropwise to the mixed solution to adjust the pH to 9.5, and then the mixed solution was heated to 50°C for hydrolysis reaction for 3h. After the hydrolysis was completed, the pH value of the solution was adjusted to 6.0 to obtain a vinyl triethoxysilane hydrolyzate.
[0048] Weigh 600g of vinyl triethoxysilane hydrolyzate, add 20g of levodopa to it and mix and stir until levodopa is dissolved, then add 400g of dimethyl sulfoxide and mix and stir to form a mixed system, then evaporate under reduced pressure to remove water in the mixed system, then add 18g of EDC hydrochloride reagent and 18g of DMAP reagent and mix and stir evenly, control the temperature of the whole system at 20±2°C, and time the reaction for 19h. After the reaction is completed, dialyze with a dialysis bag with a molecular weight cutoff of 500Da and collect the internal liquid in the dialysis bag, then purify with column chromatography, and then dry to remove water to obtain modified levodopa.
[0049] The chrome-plated parts were polished with sandpaper and rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in modified L-DOPA, and the pH of the immersion was adjusted to 8.5, and then the immersion was timed for 5 hours. After the immersion, the treated chrome-plated parts were taken out and completely immersed in ethyl methacrylate solution with a mass concentration of 38%, and then benzoyl peroxide was added according to 0.009 times the mass of ethyl methacrylate solution, mixed and stirred, and heated to 78°C, and the catalytic reaction was carried out for 7 hours. After the reaction, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in 0.1mol / L / silver nitrate solution for 23 hours to obtain the fingerprint-resistant coating of the chrome-plated parts. Embodiment 6:
[0050] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0051] 200g of vinyl triethoxysilane was dissolved in an acetone solution of equal mass, and then 1200g of deionized water was added and stirred to form a mixed solution. Sodium hydroxide solution was added dropwise to the mixed solution to adjust the pH to 9.5, and then the mixed solution was heated to 50°C for hydrolysis reaction for 3h. After the hydrolysis was completed, the pH value of the solution was adjusted to 6.0 to obtain a vinyl triethoxysilane hydrolyzate.
[0052] Weigh 600g of vinyl triethoxysilane hydrolyzate, add 20g of levodopa to it and mix and stir until levodopa is dissolved, then add 400g of dimethyl sulfoxide and mix and stir to form a mixed system, then evaporate under reduced pressure to remove water in the mixed system, then add 20g of EDC hydrochloride reagent and 20g of DMAP reagent and mix and stir evenly, control the temperature of the whole system at 20±2°C, and time the reaction for 20h. After the reaction is completed, dialyze with a dialysis bag with a molecular weight cutoff of 500Da and collect the internal liquid in the dialysis bag, then purify with column chromatography, and then dry to remove water to obtain modified levodopa.
[0053] After the chrome-plated parts were polished with sandpaper, they were rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in modified L-DOPA, and the pH of the immersion was adjusted to 8.5, and then the immersion was timed for 5 hours. After the immersion was completed, the treated chrome-plated parts were taken out and completely immersed in a 40% mass concentration of ethyl methacrylate solution, and then benzoyl peroxide was added according to 0.01 times the mass of the ethyl methacrylate solution, mixed and stirred, and heated to 80°C, and the catalytic reaction was carried out for 7 hours. After the reaction was completed, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in a 0.1mol / L / silver nitrate solution for 24 hours to obtain a fingerprint-resistant coating for the chrome-plated parts.
[0054] Comparative Example 1:
[0055] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0056] The levodopa in Example 6 was replaced by dopamine hydrochloride, and the other conditions remained the same as in Example 6.
[0057] Comparative Example 2:
[0058] A method for preparing a chrome-plated part anti-fingerprint coating comprises the following steps:
[0059] The chrome-plated parts were polished with sandpaper and rinsed with acetone solution and water three times respectively, and then dried to remove surface moisture. The pretreated chrome-plated parts were completely immersed in Tris-hydrochloric acid buffer containing levodopa with a pH value of 8.5 (the mass concentration of levodopa was 2%), and then left to stand at room temperature for 5 hours. After the immersion, the chrome-plated parts were taken out and completely immersed in ethyl methacrylate solution with a mass concentration of 40%, and then benzoyl peroxide was added according to 0.01 times the mass of ethyl methacrylate solution, mixed and stirred, and heated to 80°C for catalytic reaction for 7 hours. After the reaction, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were taken out and the surface was rinsed with ethanol. Finally, the polyethyl methacrylate-poly-levodopa-chrome-plated parts were immersed in 0.1mol / L / silver nitrate solution for 24 hours to obtain the fingerprint-resistant coating of the chrome-plated parts.
[0060] The chrome-plated anti-fingerprint coating obtained in Examples 1 to 6 and Comparative Examples 1 to 2 was immersed in boiling water for 2 hours. Immediately after immersion, it was cut into a chessboard shape (10×10, 1mm interval) with a knife. The cuts should expose the substrate. After cleaning along the diagonal direction with a brush, a pressure-sensitive tape was used to stick to the square cuts, and then the pressure-sensitive tape was torn off. The grade was evaluated according to the proportion of the coating film peeling area. The evaluation criteria are as follows: no peeling; peeling area rate is less than 5%; peeling area rate is 5% or more but less than 20%; peeling area rate is 20% or more. The adhesion test results are shown in Table 1 below.
[0061] Table 1
[0062]
[0063] 10h vaseline was evenly coated on the anti-fingerprint coating of the chrome-plated parts obtained in Examples 1-6 and Comparative Examples 1-2, and then wiped off after standing for 3 hours. The color difference change value △E before and after the experiment was tested with a colorimeter (the smaller the value, the better the anti-fingerprint performance). The results are shown in Table 2 below.
[0064] Table 2
[0065]
[0066] From the results in Table 1 and Table 2 above, we can draw the following conclusions:
[0067] (1) Embodiments 1 to 6 of the present invention improve the compactness of the surface coating of the chrome-plated part by constructing the synergistic effect between hydrogen bond cross-linking adsorption, chemical copolymerization and metal coordination, thereby achieving anti-fingerprint protection for the chrome-plated part and having good adhesion.
[0068] (2) It can be seen from Comparative Example 1 that although dopamine hydrochloride can also polymerize to form a polydopamine structure with a strong adhesion effect, since dopamine hydrochloride does not have an active group that can introduce a carbon-carbon double bond, it is impossible to form a polyethyl methacrylate structure on the surface of polydopamine when immersed in an ethyl methacrylate solution. The lack of chemical copolymerization effect and the lack of polyethyl methacrylate make it impossible to further form a dense metal coordination cross-linking effect, resulting in poor coating density, poor fingerprint resistance and poor adhesion.
[0069] (3) It can be seen from Comparative Example 2 that since poly-L-DOPA is combined with polyethyl methacrylate only by physical adsorption and metal coordination, and lacks chemical copolymerization with stronger binding force, the coating has poor density, poor fingerprint resistance and poor adhesion.
[0070] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a chrome-plated part anti-fingerprint coating, characterized in that: The preparation method comprises the following steps: After the organic siloxane coupling agent is dissolved, deionized water is added and mixed and stirred to form a mixed solution, the pH of the mixed solution is adjusted to 8.5-9.5 with an alkaline solution, and then heated to 40° C.-50° C. for reaction for 2 h-3 h to obtain a silane coupling agent hydrolyzate; After the silane coupling agent hydrolyzate is mixed with levodopa, dimethyl sulfoxide is added and stirred to form a mixed system, after the mixed system is evaporated under reduced pressure to remove water, EDC hydrochloride reagent and DMAP reagent are added and the temperature is controlled at 18° C. to 22° C. to react for 15 h to 20 h to obtain modified levodopa; The pre-treated chrome-plated part is immersed in the modified levodopa, and the pH of the immersion is adjusted to 8.0-8.5, and the immersion time is 3h-5h; After the dipping is completed, the chrome-plated part is immersed in a methacrylate solution with a mass concentration of 30% to 40%, and then an initiator is added and heated to 70°C to 80°C for reaction for 5h to 7h to obtain a polymethacrylate-poly-levodopa-chrome-plated part; The polymethacrylate-poly-levodopa-chrome-plated part is immersed in a 0.1 mol / L silver salt solution for 20 h to 24 h to obtain a fingerprint-resistant coating for the chrome-plated part; The organic siloxane coupling agent includes vinyl trimethoxy silane or vinyl triethoxy silane.
2. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The mass ratio of the organic siloxane coupling agent to deionized water is 1:4-6.
3. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The pH value of the silane coupling agent hydrolyzate is 5.5-6.
0.
4. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The mass ratio of the silane coupling agent hydrolyzate: levodopa: EDC hydrochloride reagent: DMAP reagent is 2-3: 0.1: 0.05-0.1: 0.05-0.
1.
5. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The methacrylate solution includes a methyl methacrylate solution or an ethyl methacrylate solution.
6. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The initiator includes azobisisobutyronitrile or benzoyl peroxide.
7. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The mass ratio of the methacrylate solution to the initiator is 1:0.005-0.
01.
8. The method for preparing a chrome-plated part anti-fingerprint coating according to claim 1, characterized in that: The silver salt solution includes a silver nitrate solution.
9. A chrome-plated part anti-fingerprint coating prepared by the method for preparing a chrome-plated part anti-fingerprint coating according to any one of claims 1 to 8.
Citation Information
Patent Citations
Anti-fingerprint film, glass product and preparation method of glass product
CN112877642A
Surface modification method for polymerization and crosslinking-solidification of dopamine and derivatives thereof
CN106750462A
Preparation method of environment-friendly non-chrome fingerprint-resisting passivation solution
CN108165970A